Kajian Strategi Penanganan Kawasan Kumuh di Kabupaten Bangka Tengah: Slum Upgrading Strategies in Central Bangka Regency - S Sunarti; Landung Esariti; Mardwi Rahdriawan; Dyah Putri Makhmudi (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2021)
Slum area remains as the main problem faced in urban settlement areas, especially in developing countries. Slum area in Central Bangka Regency reaches a total area of 55.92 hectares, covering 9.1% of Central Bangka Regency area. The local government formulized a strategy named Construction and Development Plan of Housing and Settlement Areas (Rencana Pembangunan dan Pengembangan Perumahan dan Kawasan Permukiman/RP3KP). The objective of this strategy is to analyze whether the strategy for slum upgrading in Central Bangka Regency has been formulated effectively. This is significant since a study of the strategy needs to be conducted before the strategy is legalized and becomes the basic framework for implementation. Quantitative technique is depicted throughout this article by comparing strategies resulted from the RP3KP document with literature driven indicators and with Law Number 1 Year 2011 on Housing and Settlements. Result shows that the plan has been formulated effectively according to three assessment aspects, namely political aspects, administrative aspects, and their suitability to Law Number 1 Year 2011. Despite, for more effective implementation, is it suggested to operationalize the strategy by formulating mechanisms and instruments for effective governance. More detailed implementation strategies shall be regulated, to not only concentrate on physical aspects, but also on non-physical aspects, such as social, economic, and demographical aspects.